Spiritualitas Islam sebagai Faktor Protektif Kesehatan Mental: Tinjauan Interdisipliner dalam Perspektif Pendidikan Agama dan Psikologi Klinis - Kendah Asih, Zwesty; Sukino, Arief; Sukmawati, Fitri (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
The mental health crisis, marked by rising cases of depression, anxiety, and loss of life meaning among adolescents and university students, requires a holistic and contextual approach. This study aims to analyze the role of Islamic spirituality as a protective factor for mental health through an interdisciplinary review combining Islamic religious education and clinical psychology perspectives. A qualitative literature review method was employed, using hermeneutic content analysis of scholarly works related to spirituality concepts, religious coping mechanisms, and their implementation in educational and psychological interventions. The findings indicate that values such as tawakkul (trust in God), patience, gratitude, and dhikr (remembrance of God) function as positive religious coping strategies that enhance individual resilience against psychosocial stressors. The integration of Islamic spirituality can be realized through the development of religious education curricula, the optimization of teachers’ roles as spiritual mentors, and the application of value-based Islamic psychotherapy. This study concludes that Islamic spirituality holds significant potential as both a preventive and curative intervention in addressing the mental health crisis within Muslim communities.